Analisis Prediksi Jumlah Pasien Rawat Inap di Rumah Sakit GMIM Siloam Sonder Menggunakan Metode Triple Exponential Smoothing - Feibe Lawalata; Eko Sediyono; Hindriyanto Purnomo (JOINTER : Journal of Informatics Engineering, 2021)
The increase in patients that occurs every month needs to be considered by every hospital, be it private hospitals or government hospitals. With the predictive value of the number of patients for each month. It is hoped that it can help hospital management, in making decisions to improve patient service facilities, especially in inpatient installations. In this study, the forecasting method used is Triple Exponential Smoothing, because this method is quite simple and also has advantages. The triple exponential smoothing method can adjust the trend of changes and seasonal components. The research was conducted at GMIM Siloam Sonder General Hospital, by taking samples in the form of data on the number of patients for the last 3 years using excel format. From the results of the analysis carried out, the forecast results obtained for the next 3 years are an increase seen from the increase in the total number of patients each year. The forecast value obtained is classified into high-accuracy forecasting because it has a MAPE value ≤ of 10%.